Three-Dimensional Mapping of Hippocampal Anatomy in Adolescents with Bipolar Disorder - Bearden, Carrie E; Soares, Jair C; Klunder, Andrea D; Nicoletti, Mark; Dierschki, Nicole; Hayashi, Kiralee M; Narr, Katherine L; Bhrambilla, Paolo; Sassi, Roberto B; Axelson, David; Ryan, Neal; Birmaher, Boris; et al. (Journal of the American Academy of Child and Adolescent Psychiatry, 2008)
The article discusses the use of three-dimensional mapping methods in children and adolescents with bipolar disorder to find out if localized alterations in hippocampal structure are exhibited. It also explores the developmental differences where the patient with bipolar disorder showed increasing hippocampal size with increasing age.